Evaluasi dan Pengelolaan Lereng Bekas Tambang Breksi Andesit Dusun Siluk Kelurahan Selopamioro Kepanewon Imogiri Kabupaten Bantul Daerah Istimewa Yogyakarta - Alwiyah, Alwiyah; Lukito, Herwin; Kristanto, Wisnu Aji Dwi; Nugroho, Nandra Eko; Suharwanto, Ir. (Jurnal Lingkungan Kebumian Indonesia, 2023)
Siluk Area, Selopamioro Village, Imogiri District, Bantul Regency, Special Region of Yogyakarta, is one of the active community mining sites. These mining activities leave slopes that are not treated or repaired, so that they become a threat to soil and/or rock mass movements for the surrounding community. One of the former mining areas in Siluk hamlet is very close to residential areas. Therefore, it is necessary to study the stability and safety factors of the slope so that they can be the basis for determining the direction of ex-mining slope management.The methods used were literature studies, field surveys and mapping, and laboratory tests. The sampling method used was the purposive sampling method. Samples taken were used for testing physical properties (content weight, moisture content, porosity, and grain size), shear angle, and cohesion. The analysis methods used are the simplified Janbu method and the descriptive analysis method to evaluate the slope of the former mine. Based on calculations and testing, it is found that the three slopes are categorized as steep slopes with a safety factor value on the central and south-north slopes of 0.156, 0.620, and 0.367. Slope management carried out involves a change in slope geometry with the cut and fill method, planting vegetation in the form of Sengon trees, and planting land cover in the form of Vertiver grass